Character Education Strategy for Visually Impaired Students of SLB Surakarta Based on Local Wisdom Values - Febian Akbar Al Husaini; Danang Purwanto; Saifuddin Zuhri (At-Tarbawi: Jurnal Pendidikan, Sosial dan Kebudayaan, 2024)
The nature of education as a shaper of the next generation of the nation requires commitment from the actors of the system. Students with visual impairments also have the same rights in receiving education including character education in Indonesia. The need for appropriate methods and media in providing material to blind students with limited vision is a challenge for educators. This study aims to find the right strategy in educating the character of blind students by using braille books that contain content about local wisdom-based character values in the city of Surakarta. The research method used in this study is descriptive qualitative. Data collection techniques were carried out through interviews with 5 blind students, 4 SLB teachers or educators, the Solo Bersimfoni community as the creator of the grapyak semanak and Lembah manah values. The data analysis used in this study used Miles & Huberman's data analysis technique. By adapting the concept of theory from Thomas Lickona who divides the character education process into 3 stages, namely moral knowing, moral feeling, and moral action. The result is a change in the behavior pattern of blind students that has been implemented previously.